Loss‐of‐function mutations in centrosomal protein 112 is associated with human acephalic spermatozoa phenotype. Issue 2 (24th November 2019) - Sha, Yanwei; Wang, Xiong; Yuan, JinTing; Zhu, Xingshen; Su, Zhiying; Zhang, Xuequan; Xu, Xiaohui; Wei, Xiaoli
Abstract: Acephalic spermatozoa, characterized by the headless sperm in the ejaculate, is a rare type of teratozoospermia. Here, we recruited two infertile patients with an acephalic spermatozoa phenotype to investigate the genetic pathology of acephalic spermatozoa. Whole‐exome sequencing analysis was performed and found mutations in CEP112 in the two patients: homozygous mutation c.496C > T:p.(Arg166X) in exon 5 from P1; and the biallelic mutations c.2074C > T:p.(Arg692Trp) in exon 20 and c.2104C > T:p.(Arg702Cys) in exon 20 from P2. Sanger sequencing confirmed the CEP112 mutations in the two patients. In silico analysis revealed that these CEP112 mutations are deleterious and rare, and all the mutations impact the coiled‐coil domain of CEP112, which may affect the protein function. The c.496C > T:p.Arg166X resulted in a truncated CEP112, which was verified by the mutation expression plasmid. The CEP112 expression was significantly reduced in the P2, suggesting the biallelic mutations c.2074C > T and c.2104C > T may affect the function and stability of CEP112. Therefore, we speculate that the loss‐of‐function mutations in CEP112 may be account for the human acephalic spermatozoa phenotype. Abstract : Loss‐of‐function mutations in CEP112 were identified from two infertile patients with acephalic spermatozoa. The nonsense mutation c.496C > T produces a truncated CEP112 protein and the biallelic mutations c.2074C > T and c.2104C > T may affect the coiled‐coil domain of CEP112 . The expression of CEP112 protein level was reduced significantly in the patients' spermatozoa.